Peran Dakwah Melalui Media Cetak Untuk Pengembangan Masyarakat Islam (Studi Terhadap Peran Majalah Suara Hidayatullah Lampung) - Kamil, Pajrun (Institut Agama Islam Negeri (IAIN) Curup, 2018)
Hidayatullah's voice magazine is an Islamic magazine managed by PT. Lentera Jaya Abadi, both of which are under the auspices of the Hidayatullah Mass Organization (ORMAS). Its presence has supported the missionary movement of the Hidayatullah Islamic Boarding School throughout Indonesia, especially conveying information about Islamic boarding schools programs to a broad audience. Along with the progress of the Hidayatullah Islamic Boarding School, the magazine became the largest and widest Islamic magazine in its distribution in Indonesia. The role of Hidayatullah's voice magazine in the development of the Islamic community is quite significant, as evidenced by the many representatives of the Hidayatullah pesantren, while the role of this magazine includes: as a communicator, motivator and facilitator. The focus of this research is how is the role of Hidayatullah's voice magazine in the development of Islamic society? What are the supporting factors and obstacles in developing Islamic society? The purpose of this study is to analyze the role of Hidayatullah's voice magazine in community development, and analyze what factors are supporting and inhibiting it. In this study the authors used qualitative research, it is hoped that with this method able to reveal facts in depth, researchers conducted structured and unstructured interviews with the resource persons namely the administrators of the Hidayatullah Voice Magazine and their readers. And supported by documentation data and direct observation. The conclusion of this study is First. The role of Hidayatullah Voice Magazine as a communicator is to communicate or socialize related to Islamic Community Development programs, as a motivator, which is to provide motivation to preachers in various remote areas, as facilitators, who also facilitate the preachers both within the Hidayatullah Community Organization. and other Islamic ORMAS in the process of developing Islamic societies. The two supporting factors of Hidayatullah's voice magazine in the development of the Islamic community are the presence of a network of militant cadres throughout Indonesia and have loyal readers. While the inhibiting factors are lack of funds to develop productive businesses and the lack of professional human resources (SDI).